Pedagogical and evaluative competencies for the 21st century in molecular biology education and their relationship with honors programs: a systematic literature review - Pérez Zúñiga, Ricardo; Martínez García, Mario; Campos-Valdez, Marina; Sánchez-Orozco, Laura V. (Frontiers in Education, 2025)
IntroductionPedagogical and evaluative competencies for the 21st century are essential in molecular biology. Literature suggests that teaching methods should assess both knowledge and disciplinary skills, as this approach is a prerequisite for student employability in biomolecular sciences.MethodsIn this systematic review, we conducted a search in Web of Science and Scopus, selecting 55 studies that met the inclusion criteria for the development of this research. The keywords used in WoS and Scopus were “molecular biology” and “students,” limited to articles published between 2020 and 2024.ResultsThis study identified a set of key competencies for the practice of molecular biology. However, it was observed that other equally relevant competencies received less attention in the analyzed reports. Honors programs implemented by universities promote innovative methodologies and technologies to enhance academic performance in molecular biology. These programs also encourage active teaching, which fosters students’ overall development.ConclusionThe most frequently noted molecular biology competencies were critical thinking, collaboration, problem-solving, communication, and creativity. In contrast, other important skills such as research, reading, self-directed learning, motivation, and digital literacy were less emphasized, despite their relevance and connection to honors programs. In terms of teaching modalities, the face-to-face laboratory teaching was the most highly valued for its practical approach, followed by the hybrid approach. The traditional mode ranked third, while the virtual mode, despite its advantages, came in fourth. Desktop-based exams predominate as an evaluative tool, but there is a gap in this approach, since all the evaluation tools detected in this study mainly measure theoretical knowledge, omitting competency evaluation. This contradiction is relevant, as today’s employers demand precisely such competencies. Implementing honors programs is one way to address this gap by focusing on developing skills that align with current labor demands.